PREDICTING IN-HOSPITAL MORTALITY AFTER BLUNT THORACO-ABDOMINAL TRAUMATIC INJURY USING SHOCK INDEX - SHAIKH, SN; ZAHEER, F; KHAN, H; MAQBOOL, N; SHAKEEL, B; SHAIKH, S (Biological and Clinical Sciences Research Journal, 2023)
Assessing the usefulness of the Shock Index (SI) in isolated blunt torso (thoraco-abdominal) trauma and its effects on resuscitation and predicting mortality is crucial. In this prospective observational study conducted at Ruth K.M. Pfau Civil Hospital, Karachi, individuals aged 16 years or older presenting with isolated thoraco-abdominal trauma were studied. Basic clinical assessments, including the measurement of SI, were carried out, and patients were resuscitated according to protocol. Another set of vitals was taken three hours after resuscitation. Patient progress in the hospital was followed until death or discharge. Both values of SI and DSI were plotted against the patient’s outcome. The results showed that values of SI remained elevated even after three hours of resuscitation in the non-survivors group of trauma patients. Furthermore, rates of ICU admissions and surgical interventions were also high among non-survivors. Therefore, this study concludes that SI is an essential factor in predicting mortality in blunt thoraco-abdominal traumatic injuries.